(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
Self-compacting concrete (SCC) is a concrete that can be installed and compacted with or without vibration, without segregation or bleeding, under its weight. Nanotechnology gives materials unique performance, and over the past 20 years, significant efforts have been created to incorporate nanoparticles (NPs) into SCC to enhance functionality and generate SCC with superior characteristics. This improves the proper filling and, consequently, the good structural performance of the restricted areas and the reinforced structural components. With the advantages of SCC in construction engineering, it has become increasingly important in recent years. Nanoparticles are promising substances, and several investigators have employed nanoparticles in SCC to enhance the fresh and hardened microstructure properties. Because of their large surface area, nanomaterials speed up the development of C-S-H gel while improving the pore structure of concrete. The present review paper reviews the impacts of various nanoparticles on the most significant fresh and mechanical characteristics of various SCC composites. As stated by the study’s findings, NPs can have a bright future in creating high-performance SCC composites that the construction sector can use effectively because of a notable improvement in workability and mechanical strength.